The Dublin Regulation: Dimensions, Problems and Perspectives - Demerouti, Sofia (HAPSc Policy Briefs Series, 2020)
Over the last 20 years, with the development of the Common European Asylum System, the policymaking towards asylum seekers has transposed to the European Union. EU’s ambition though to build a harmonized asylum system differs from reality and the injustices among Member States led to the deep crisis of the Dublin Regulation. This policy brief, examines the process of the Dublin Regulation, the problems that are still being confronted and the legislative framework of the regulation. The paper concludes with the proposal of recommendations and perspectives that could lead to a deeper integration of the system.